Pemberdayaan Pengembangan Inovasi Produk bagi UMKM Aneka Kue Almira - Hermanto, Florentina Elena; Lisha, Lisha; Anwar, Cayla Latisha; Ahmad, Faizal (Journal Pemberdayaan Masyarakat Indonesia, 2024)
This paper explores about the empowerment process of innovation development for the rural micro-business partner, Aneka Kue Almira that located in Cilaja Village, Kuningan Regency. The purpose of this empowerment activity is to enhance the partner's understanding of the importance of product innovation and the stages they must go through. In addition, this activity is expected to strengthen the business partner's skills through collaborative practices carried out together with the community service team. The empowerment activities adopt a participatory approach, involving business owners, to develop sustainable innovation strategies that enhance competitiveness and market reach. The results of this empowerment showed the creation of understanding and skills in making products based on research or market desires. Moreover, a new innovative product was created, cake pops, aimed at the school children market segment. This innovation development model for small businesses can serve as a reference for similar businesses in other rural areas.